The extent of physical and psychological workplace violence experienced by prehospital personnel in Denmark: a survey - Brit Schøsler; Frederik Stuhr Bang; Søren Mikkelsen (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Workplace violence against healthcare workers has been a well-known problem for more than 40 years. This problem is also relevant for prehospital personnel who are at risk of physical and/or psychological violence during work. Violence and threats of violence can have physical and psychological consequences, including personal challenges in their everyday life, use of sick days, reports, and the need for professional help. Therefore, this study aimed to describe the extent of and subsequent reporting of physical and psychological workplace violence toward the prehospital healthcare workers in Denmark in a two-year period. Moreover, we wanted to elucidate any possible effect of workplace violence on the private and professional lives of the prehospital healthcare personnel. Methods A nation-wide survey where a validated anonymised questionnaire was directed to all of the approximately 4500 Danish prehospital healthcare workers. Results Out of 584 complete responses we found that 47.4% had experienced psychological violence on the job whereas 25.7% had experienced physical violence on the job within the past two years. The perpetrators were mainly patients or relatives of the patients. Physical violence was mostly reported as punching, pushing, and kicking, while psychological violence included threats of violence and other intimidation. After experiencing violence the respondents reported both physical and psychological harm, which for some prehospital healthcare workers had consequences for their professional and/or personal life. Furthermore, some prehospital healthcare workers reported that the violence had resulted in some patients receiving worse treatment afterwards. We found that violence was rarely reported to either employers or the police, because respondents believed the events were not important enough to merit reporting, or because a report was not considered to make any difference to the healthcare worker. The survey demonstrates that, as a minimum, at least one healthcare worker in 30 and one healthcare worker in 16 has been exposed to episodes of violence and threats of violence within the last two years. Conclusion We suggest that the prehospital organisations emphasise reporting future episodes of physical and/or psychological violence. Knowing the extent of the problem is a prerequisite for addressing, debriefing, and/or other psychological follow-up. Trial registration N/A.